MENCEGAH DAMPAK DARURAT KEKERASAN PADA ANAK INDONESIA - Hidaayah, Nur (Jurnal Ilmiah Kesehatan, 2015)
Child abuse occur in the conditions, places, people closest to where the child should feel secure that home, school and community environments. According to UNICEF that violence against children in some countries can be socially acceptable, it is allowed and is not seen as something rude. Some factors contributing to violence include: witnessing parental violence while still childhood, aggressive attitude towards the child, wife or husband, and behaved aggressively towards children and the environment that supports the violence recurs. Children who experience repeated violence much risk of adverse impacts that they showed chronic stress, including difficulties in school and problems with concentration. Things do not have to happen is depression to suicidal behavior. Help prevent the necessary co-operation of various elements of parents, educators, family leaders, community leaders, community organizations, peers, program managers across relevant sectors. Indispensable role of the academia, professional organizations, Society of Social Institutions and law enforcement officials.